2015
DOI: 10.1016/j.psychres.2014.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measurement invariance of the Beck Scale for Suicide Ideation

Abstract: In mental health care, both clinical and scientific decisions are based on within-subject comparisons of test scores on the same self-report questionnaire at different points in time. To establish the validity of test score comparisons over time, longitudinal measurement invariance should be established. The current study tested whether the 19 item Beck Scale for Suicide Ideation (BSS) is measurement invariant (MI) over time. As the first five items of the scale are often used to screen for the presence of sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…The psychometric properties of the BSS are well-established (de Beurs, Fokkema, de Groot, de Keijser, & Kerkhof, 2015) and the internal consistency of the scale in the current study was found to be good (α = .87).…”
Section: Methodssupporting
confidence: 57%
“…The psychometric properties of the BSS are well-established (de Beurs, Fokkema, de Groot, de Keijser, & Kerkhof, 2015) and the internal consistency of the scale in the current study was found to be good (α = .87).…”
Section: Methodssupporting
confidence: 57%
“…Five studies in different psychiatric populations, using self‐report and/or clinician‐report instruments, found response shift indications: Barbosa‐Leiker, McPherson, Mamey, Burns, and Roll (); Czobor and Volavka (); Elhai et al (); Fried et al (); Boucekine et al (). However, no response shift was found in the mental health studies by Quilty et al () with clinician‐rated scale and by de Beurs, Fokkema, de Groot, de Keijser, and Kerkhof () with self‐report scale.…”
Section: Discussionmentioning
confidence: 91%
“…Internal reliability, test-retest stability and validity for the BSS have been established (Brown, 2001;de Beurs, Fokkema, de Groot, de Keijser, & Kerkhof, 2015). The severity of suicidal ideation is calculated by summing the ratings of the first 19 items.…”
Section: Methodsmentioning
confidence: 99%